Identification of differentially expressed ripening-related cDNA clones from tomato (Lycopersicon esculentum) using tomato EST array - Anjanasree, K; Srivastava, A; Handa, A; Bansal, K (2005)
Qualitative changes in ripening tomato fruits are invariably associated with differential gene expression mediated by the phytohormone ethylene and certain developmental and environmental cues. In the present study, we compared, using the tomato expressed sequence tag (EST) array, the cDNA expression patterns of 'breaker'-stage fruits of two cultivars, Pusa Ruby and Pusa Uphar (DT-2), which significantly differed in their rate of ripening and shelf-life. Screening of bacterial EST microarray filters revealed the presence of 1536 differentially expressed cDNA clones, among which 200 were found up-regulated and 42 down-regulated. The results revealed significant differences in the ripening-related gene expression between the two cultivars which differed in the rate of ripening, and demonstrated the utility of EST-screening approaches as an initial step towards identifying key genes that affect fruit storability, shelf-life and post-harvest characteristics.